Value Proposition Testing For Private Event Package at My Kopi O Serang - Wita Nidia Hanifah; Ilma Aulia Zaim (Journal Research of Social Science, Economics, and Management, 2025)
This research redefines the value proposition of the Private Event Package at My Kopi O Serang to align with customer needs and preferences. The study aims to assess the current offering’s compatibility with customer expectations, realign it to reflect customer jobs, pains, and gains, and propose a more compelling value proposition. Using a mixed-method approach, including Thematic Analysis, Empathy Mapping, and quantitative validation through Problem-Solution Fit and Product-Market Fit tests, the research identifies two validated value propositions: (1) Exclusive Event Experience with Personalized Service for those seeking premium, private events, and (2) Price-effective Event Package for customers who prioritize affordability and value. To meet these needs, a tiered model is proposed: Silver and Gold packages for budget-conscious customers, and Platinum and Diamond for premium-seeking ones. The research also suggests creating a sense of exclusivity through semi-private arrangements and attentive service. This hybrid value proposition moves away from a one-size-fits-all approach to a segmented, data-driven offering, positioning My Kopi O Serang to cater to both premium and value-conscious customers in a competitive market.